A geochemical and field study of the Ingeli and Horseshoe lobes, Mount Ayliff Complex, South Africa, and its potential for magmatic suphide ores - Maier, Wolfgang D. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2006.